2018
DOI: 10.3389/fnagi.2018.00162
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 Inhibitory Peptide Prevents Loss of Dopaminergic Neurons and Alleviates Behavioral Changes in an MPTP Induced Parkinson’s Disease Mouse Model

Abstract: Parkinson’s disease (PD) is one of the most affected neurodegenerative diseases in the world. Deregulation of cyclin-dependent kinase 5 (Cdk5) is believed to play an important role in neurodegenerative diseases including PD. p25 is a cleavage peptide of p35, a physiologic activator of Cdk5. p25 combines to Cdk5 and leads to the hyperactivity of Cdk5, which in turn hyperphosphorylates downstream substrates and leads to neuroinflammation and apoptosis of neurons. Previously, we have demonstrated that adeno-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Thus, it has been proposed that Cdk5 activity inhibition can be a potential promising therapeutic strategy for AD treatment. Indeed many studies have shown that the pharmacological or the genetic inhibition of Cdk5 activity can prevent synaptic loss and neuronal death and exert some protective effect in mouse models of AD and PD (Lau and Ahlijanian, 2003 ; Piedrahita et al, 2010 ; Liu et al, 2016 ; Seo et al, 2017 ; He et al, 2018 ). However, preclinical or clinical trials with some Cdk5 inhibitors were not promising due to severe side effects or off-target effects (Cicenas et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been proposed that Cdk5 activity inhibition can be a potential promising therapeutic strategy for AD treatment. Indeed many studies have shown that the pharmacological or the genetic inhibition of Cdk5 activity can prevent synaptic loss and neuronal death and exert some protective effect in mouse models of AD and PD (Lau and Ahlijanian, 2003 ; Piedrahita et al, 2010 ; Liu et al, 2016 ; Seo et al, 2017 ; He et al, 2018 ). However, preclinical or clinical trials with some Cdk5 inhibitors were not promising due to severe side effects or off-target effects (Cicenas et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of a pan-Cdk synthetic inhibitor flavopiridol attenuates MPTP-induced degeneration of nigral dopaminergic neuron and reduces motor impairments in this model [ 131 ]. Viral-mediated expression of dominant-negative Cdk5 or a peptide inhibitor of Cdk5 prevents the death of dopaminergic neurons in the MPTP mouse model [ 131 , 132 ]. Similarly, a Cdk5 peptide inhibitor blocks Cdk5 hyperactivity and promotes dopaminergic neuronal survival in the nematode worm C. elegans after exposure to paraquat [ 133 ].…”
Section: Dysregulation Of Cdk5: Calpain-dependent Proteolytic Cleavage Of P35 To P25mentioning
confidence: 99%
“…Another study performed in a PD mouse model demonstrated that specific inhibition of Cdk5, by adeno-associated virus serotype-9 (AAV9) mediated Cdk5 inhibitory peptide (CIP), was protective against loss of dopaminergic neurons in the substantia nigra. Importantly, treatment with this inhibitor resulted in improved motor and anxiety-like symptoms in these mice [ 71 ]. Moreover, it was reported that inhibition of Cdk5 activity enhanced CaMKII autophosphorylation/activation in cultured neurons [ 72 ], which suggests that Cdk5 inhibitors can be considered as potential drugs in the treatment of PD symptoms.…”
Section: Cam-dependent Protein Kinase II and Its Substratesmentioning
confidence: 99%